2017
DOI: 10.3747/pdi.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Outcomes in Nephrology—Peritoneal Dialysis (SONG-PD): Study Protocol for Establishing a Core Outcome Set in PD

Abstract: Background Worldwide, approximately 11% of patients on dialysis receive peritoneal dialysis (PD). Whilst PD may offer more autonomy to patients compared with haemodialysis, patient and caregiver burnout, technique failure, and peritonitis remain major challenges to the success of PD. Improvements in care and outcomes are likely to be mediated by randomised trials of innovative therapies, but will be limited if the outcomes measured and reported are not important for patients and clinicians. The aim of the Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 66 publications
1
58
0
1
Order By: Relevance
“…This study will inform the development of a core outcome set for trials in PD, which incorporates the priorities of all stakeholders as part of the Standardized Outcomes in Nephrology (SONG) initiative (41). To date, the SONG initiative has successfully developed core outcome sets in hemodialysis and kidney transplantation, using patient and caregiver priorities identified through nominal group technique and Delphi surveys (8,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…This study will inform the development of a core outcome set for trials in PD, which incorporates the priorities of all stakeholders as part of the Standardized Outcomes in Nephrology (SONG) initiative (41). To date, the SONG initiative has successfully developed core outcome sets in hemodialysis and kidney transplantation, using patient and caregiver priorities identified through nominal group technique and Delphi surveys (8,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…For this innovation to have merit it clearly needs to impact on clinically meaningful outcomes such as peritoneal integrity, frequency of infection, residual renal function and technique survival. Occurrence of peritonitis is a key outcome measure which has been prioritised by patients and health care professionals through the SONG-PD initiative (9). All four peritonitis episodes in the study reported here occurred in the control group with none occurring during the intervention, however too much significance should not be placed on this because of the small sample size.…”
Section: The Potential Benefits Of Alanyl-glutamine Supplementationmentioning
confidence: 81%
“…62,63 Such standardization of outcomes was previously recognized for research by the SONG initiative. [20][21][22][23] Our work is a multinational effort to recommend a standardized minimum set of health outcome measures for use in routine clinical practice across different settings worldwide, incorporating PROMs that are important to a broad spectrum of patients with CKD, including those with pre-ESKD stages.…”
Section: Discussionmentioning
confidence: 99%
“…For research, the need for standardization of outcome measurement in CKD was previously recognized by the Standardised Outcomes in Nephrology (SONG) initiative. [20][21][22][23] To support the development of a standardized outcome set in CKD for integration into routine clinical practice, the International Consortium for Health Outcomes Measurement (ICHOM; www.ichom.org) convened an international multidisciplinary working group of experts and patient representatives. The aim of the project was to propose a standardized minimum set of patient-centered outcomes for CKD, including patient-reported outcome measures (PROMs) and casemix factors to increase the usefulness of comparisons across treatment modalities and institutions, targeted for clinical use to enable standardization of health outcome measurement in routine clinical practice in different settings.…”
Section: Introductionmentioning
confidence: 99%